Союз 17 Октября и крестьянский вопрос - Wiśniewski, Edward (Zeszyty Wiejskie, 2016)
In November 1905, the Union of October 17 was founded by liberal conservatists. In the party’s initial programme, not a hint of the problems of peasantry appeared. Not until the first elections of State Duma were organized, had the first vague proposals of agrarian reforms appeared. The political effort in question proved futile, which was reflected by the election results: the Octobrist Party won only 13 mandates. Only after that failure did the Union realize that without the support of the peasants, no political success could be possible and its members began working on amending their political programme with the peasant issue involved.